2003
DOI: 10.1515/znc-2003-5-613
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Galantamine Hydrobromide

Abstract: The antioxidant properties of galantamine hydrobromide ((4α,6 )-4a,5,9,10,11,12-hexahydro-3-methoxy-11-methyl-6H-benzofuro[3a,3,2-ef][2]benzazepin-6-ol hydrobromide) were studied in vitro, using luminol-dependent chemiluminescence and spectrophotometry. It was found that this compound was a scavenger of reactive oxygen species (ROS). By comparing the antioxidant effects of galantamine ((4α,6 )-4a,5,9,10,11,12-hexahydro-3-methoxy-11-methyl-6H-benzofuro[3a,3,2-ef][2]benzazepin-6-ol), galantamine hydrobromide, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Considering that the first administration of the drug in this protocol was not until 3 h after ischemia, galantamine could be protecting against the cell death caused by oxygen radicals generated during the reperfusion period. In fact, galantamine is a molecule with antioxidant properties (Traykova et al, 2003). It is well documented that reperfusion after brain ischemia triggers the overproduction of reactive oxygen species that can exacerbate cell death (McCord, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the first administration of the drug in this protocol was not until 3 h after ischemia, galantamine could be protecting against the cell death caused by oxygen radicals generated during the reperfusion period. In fact, galantamine is a molecule with antioxidant properties (Traykova et al, 2003). It is well documented that reperfusion after brain ischemia triggers the overproduction of reactive oxygen species that can exacerbate cell death (McCord, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…According to Traykova et al 31 , the FT-IR spectrum of GH is very characteristic. It shows several bands, of which the most characteristic are: the stretching O-H bond vibration of the enol group (C ¼ C-O-H) at 3559 cm À1 and the band which results from overlapping of the stretching vibration of physically adsorbed hydrogen bonded water and hydrogen bonded N-H Figure 2.…”
Section: Ft-ir Spectrometrymentioning
confidence: 99%
“…The multiple neuroprotective effects of melatonin, which include its anti-apoptotic, anti-inflammatory, and antioxidant actions, are mediated by both receptor and nonreceptor pathways. On the other hand, it has been demonstrated that the neuroprotective effect of galantamine, a wellknown AChEI used to treat AD, is associated to its ability to act on nicotinic receptors [28] and to its antioxidant effect [38]. Hence, both drugs could be good candidates to combat AD.…”
Section: Discussionmentioning
confidence: 99%